PENGARUH TEMPERATUR WATER COOLANT DAN AIR BIASA TERHADAP KONSUMSI BAHAN BAKAR PADA MESIN BENSIN DAIHATSU TARUNA EFI 1.6 - Sukri, Sukri; Syamsuddin, Usman; Musthofa, Imron; Artika, Kurnia Dwi; Merpatih, Merpatih (POLITALA PRESS, 2025)
Vehicles with conventional engines produce heat from combustion in the engine, so that the engine temperature is stable, a radiator water system is needed. The purpose of this study was to determine the effect of water coolant and plain water temperatures on fuel consumption. The method used was to test 3 variations of engine speed, namely 1000, 1500 and 2000 rpm on fuel consumption and engine temperature. The results obtained showed that the average fuel consumption was the same when using water coolant and plain water at an engine speed of 1000 rpm and the water coolant temperature was 3 oC lower than the temperature of plain water. While the average fuel consumption when using water coolant was 17 mL lower than using plain water at engine speeds of 1500 rpm and 2000 rpm, with a temperature drop of 1-3 oC. So, fuel consumption and temperature were lower when using water coolant than when using plain water.